Effect of ball milling parameters on the synthesization of carbon nanotube aluminium nano composite - Abdullah, Umma; Maleque, Md. Abdul; Yaacob, Iskandar Idris; Ali, Mohammad Yeakub (Trans Tech Publications, Switzerland, 2013)
Recently, carbon nanotubes (CNTs) are attracting much interest as fibrous materials for reinforcing aluminium matrix composites due to unique properties such as high strength, elastic modulus, flexibility and high aspect ratios. However, the quality of the dispersion is the major concern factor which determines the homogeneity of the enhanced mechanical and tribological properties of the composite. This work study and characterized the nano-composite prepared with different weight percentage of CNT in aluminium matrix using powder metallurgy route under high energy planetary ball milling operations. The ball milling was performed for three hours at different milling speeds and under controlled atmosphere. The experimental results showed homogeneous dispersion of CNTs in aluminium matrix at 300 rpm. The preliminary mixing of CNTs and aluminium powder in a tube via manual shaking could be the main contributing factor in achieving uniform dispersion of CNT in aluminium matrix after ball milling. The addition of ethanol as a process control agent reduced the agglomeration of CNTs in the matrix. Control atmosphere during milling also prevented the formation of inter metallic compounds such as aluminium carbide in the composite.